2019
DOI: 10.1007/s12105-019-01073-7
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Bilateral External Auditory Canal Cochlin Aggregates (“Cochlinomas”) with Multifocal Amyloid-Like Deposits, Associated with Sensorineural Hearing Loss and a Novel Genetic Variant in COCH Encoding Cochlin

Abstract: First report of bilateral external auditory canal cochlin aggregates ("cochlinomas") with multifocal amyloid-like deposits, associated with sensorineural hearing loss and a novel genetic variant in COCH encoding cochlin Running head: Amyloid-like cochlin deposits in EACs Precis: We present the first case of deafness associated with bilateral external auditory canal cochlin deposits, evidence suggestive of cochlin-derived amyloid formation, and a novel COCH variant. Our findings reveal a new pathologic manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The clinical manifestations of our proband, III.3, which showed mild vestibular symptoms accompanied by negative results in nearly all vestibular function assessments, were compatible with our molecular basis findings. Generally speaking, most of the affected subjects in Family621 did not manifest vestibular symptoms; this phenomenon was quite similar to that of subjects affected by the other C-terminal COCH variants (p.I541F, p.C542R, p.C542Y, and p.C542F [21][22][23]41]). However, the onset of hearing loss in p.D544Vfs*3 variant carriers was relatively late compared to those of the other C-terminal COCH variants (which varied from childhood to 20s), which may be due to its relatively greater distance from the critical C542 residue.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The clinical manifestations of our proband, III.3, which showed mild vestibular symptoms accompanied by negative results in nearly all vestibular function assessments, were compatible with our molecular basis findings. Generally speaking, most of the affected subjects in Family621 did not manifest vestibular symptoms; this phenomenon was quite similar to that of subjects affected by the other C-terminal COCH variants (p.I541F, p.C542R, p.C542Y, and p.C542F [21][22][23]41]). However, the onset of hearing loss in p.D544Vfs*3 variant carriers was relatively late compared to those of the other C-terminal COCH variants (which varied from childhood to 20s), which may be due to its relatively greater distance from the critical C542 residue.…”
Section: Discussionsupporting
confidence: 62%
“…Currently, several studies have demonstrated that vWFA domain variants also cause high-molecular-weight cochlin aggregation in cells [20]. However, recent studies detected COCH variants at the protein's C-terminus that co-segregated with DFNA9 hearing impairment in pedigrees, suggesting that proper function of the non-domain region of cochlin was also required for normal hearing [21][22][23]. These studies also reported that ADNSHL patients with COCH p.I541F, p.C542Y, and p.C542F variants have no vestibular symptoms [24].…”
Section: Introductionmentioning
confidence: 99%
“…After full-text screening, 48 studies met the eligibility criteria and together reported on 27 different COCH variants ( Figure 1 and Figure S1 ). Thirty-seven of these studies were retrospective family studies, describing the (audiovestibular) phenotype of COCH variants [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Eleven of the included studies were not primarily genotype-phenotype studies but validation studies of genetic analyses or histopathological studies [ 9 , 56 , 57 , 58 , 59 , 60 , 61 , 62...…”
Section: Resultsmentioning
confidence: 99%